The Influence of Financial Literacy, Financial Anxiety, Fintech Payment, Financial Attitude, and Lifestyle on Students’ Financial Behavior in Purwokerto - Diva Anur Pramesti; Siti Muntahanah; Dian Safitri Pantja Koesoemasari (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the influence of financial literacy, financial anxiety, fintech payments, financial attitude, and lifestyle on the financial behavior of undergraduate students in Purwokerto. Understanding the factors that shape students’ financial behavior is increasingly important in the digital era, where financial knowledge, psychological conditions, technological innovation, and consumption patterns collectively influence financial decision-making. This study contributes to the literature by providing empirical evidence on the combined effects of cognitive, psychological, technological, and behavioral factors on students’ financial behavior. A quantitative survey design was employed, and data were collected through structured questionnaires from 100 active undergraduate students who had completed at least their third semester using purposive sampling. The data were analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that the regression model is statistically significant (F = 76.858, p < 0.001) and explains 80.3% of the variance in students’ financial behavior (R² = 0.803). Financial literacy, fintech payments, financial attitude, and lifestyle have significant positive effects on financial behavior, whereas financial anxiety has a significant negative effect. These findings provide practical insights for universities and policymakers in developing effective financial education programs and promoting responsible financial decision-making among students. However, this study is limited by its use of purposive sampling and data collected from undergraduate students in a single geographic area, which may limit the generalizability of the findings. Future studies are recommended to examine additional determinants of financial behavior across broader populations and different educational contexts.